Metal Ion-Chelated Tannic Acid Coating for Hemostatic Dressing - Song, Bing (Materials (Basel), 2019)
Tannic acid (TA), a high-molecular-weight polyphenol, is used as a hemostasis spray and unguent for trauma wound remedy in traditional medical treatment. However, the use of tannic acid on a large-area wound would lead to absorption poisoning. In this work, a TA coating was assembled on a quartz/silicon slide, or medical gauze, via chelation interaction between TA and Fe(3+) ions and for further use as a hemostasis dressing. Protein adsorption on the TA coating was further investigated by fluorescence signal, ellipsometry analysis and sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). The adsorbed bovine serum albumin (BSA), immunoglobulin G (IgG) and fibrinogen (Fgn) on the TA coating was in the manner of monolayer saturation adsorption, and fibrinogen showed the largest adsorption. Furthermore, we found the slight hemolysis of the TA coating caused by the lysed red blood cells and adsorption of protein, especially the clotting-related fibrinogen, resulted in excellent hemostasis performance of the TA coating in the blood clotting of an animal wound. Thus, this economic, environmentally friendly, flexible TA coating has potential in medical applications as a means of preparing novel hemostasis materials.